Hardware architecture for real-time crossbar switching using genetic algorithm approach - Ding, Sheng Hua (2008)
In time-multiplexed communication systems, crossbar switches route communication traffic from input to output where fixed length message packet is transferred from the source to the destination. With proper traffic scheduling for time-multiplexed crossbar switches, the throughput of data packets can be maximized and at the same time minimizing packet blocking probability and packet waiting time.